Formulasi dan uji agent untuk produksi light concrete - Farah Dwi Vaniya; Desri Kesumaning; Izarul Machdar (Universitas Syiah Kuala, 2020)
In Indonesia, one of the most common problems is earthquakes. Indonesia is an earthquake-prone area that requires special materials for building construction. Lightweight concrete or light-concrete is one of the alternatives that can be applied to replace conventional concrete that is relatively heavier in the earthquake areabuildings construction. Light-concrete is not only strong, but also prudent in using aggregate, so it can be used for areas where there is not sufficient aggregate. One of the materials of light-concrete is a foaming agent that serves to create gas / air bubbles in cement mortar so that there are many pores in the concrete that can reduce concrete density to make the concrete lighter. The use of foaming agent has been widely applied, but the foaming agent is still imported from abroad. This study is conducted to meet the needs of cheaper foaming agent that can be obtained domestically. The basic components of the foaming agent comprise a mixture of solvent and additive surfactants. In this study, synthetic surfactants (sodium dodecyl sulfate), solvent propylrne glycol, aquades and NaCl were used. From the various concentrations of the above components, measurements of surface tension, foamness, foam density, and average grain size of the foam were conducted to obtain the best solution formulations.